Aerobic exercise interventions reduce blood pressure in patients after stroke or transient ischaemic attack: a systematic review and meta-analysis. Issue 24 (9th May 2018) - Wang, Cheng; Redgrave, Jessica; Shafizadeh, Mohsen; Majid, Arshad; Kilner, Karen; Ali, Ali N
Abstract : Objective: Secondary vascular risk reduction is critical to preventing recurrent stroke. We aimed to evaluate the effect of exercise interventions on vascular risk factors and recurrent ischaemic events after stroke or transient ischaemic attack (TIA). Design: Intervention systematic review and meta-analysis. Data sources: OVID MEDLINE, PubMed, The Cochrane Library, Web of Science, The National Institute for Health and Care Excellence, TRIP Database, CINAHL, PsycINFO, SCOPUS, UK Clinical Trials Gateway and the China National Knowledge Infrastructure were searched from 1966 to October 2017. Eligibility criteria: Randomised controlled trials evaluating aerobic or resistance exercise interventions on vascular risk factors and recurrent ischaemic events among patients with stroke or TIA, compared with control. Results: Twenty studies (n=1031) were included. Exercise interventions resulted in significant reductions in systolic blood pressure (SBP) −4.30 mm Hg (95% CI −6.77 to −1.83) and diastolic blood pressure −2.58 mm Hg (95% CI −4.7 to −0.46) compared with control. Reduction in SBP was most pronounced among studies initiating exercise within 6 months of stroke or TIA (−8.46 mm Hg, 95% CI −12.18 to −4.75 vs −2.33 mm Hg, 95% CI −3.94 to −0.72), and in those incorporating an educational component (−7.81 mm Hg, 95% CI −14.34 to −1.28 vs −2.78 mm Hg, 95% CI −4.33 to −1.23). Exercise was also associated with reductions in total cholesterol (−0.27 mmol/L, 95% CI −0.54 to 0.00), but not fasting glucose or body mass index. One trial reported reductions in secondary vascular events with exercise, but was insufficiently powered. Summary: Exercise interventions can result in clinically meaningful blood pressure reductions, particularly if initiated early and alongside education.